Providing Care for Cancer Survivors in Integrated Health Care Delivery Systems: Practices, Challenges, and Research Opportunities - Chubak, Jessica (American Society of Clinical Oncology, 2012)
PURPOSE: Optimal approaches to cancer survivorship care are needed. This study sought to identify practices, barriers, and research opportunities in meeting the care needs of cancer survivors in integrated health care delivery systems. METHODS: This study was conducted at 10 sites within the Cancer Research Network, a National Cancer Institute–funded consortium of integrated health care delivery systems providing care for nearly 11 million enrollees. We identified 48 clinical leaders, administrators, and providers in oncology, primary care, nursing administration, and specialty care. Forty (83%) completed semi-structured, audio-recorded, transcribed telephone interviews, which we analyzed using an immersion-crystallization approach. RESULTS: Respondents were aware of the needs of cancer survivors and the difficulties they face in transitioning from treatment to follow-up care. Respondents from all sites reported that oncology and primary care are jointly responsible for the care of cancer survivors, often through the use of electronic medical records. Many respondents were not familiar with standardized survivorship care plans. Only two sites had formal cancer survivorship programs in place, and two were developing such programs. Respondents at sites with and without programs acknowledged existing gaps in evidence on the effectiveness of formal survivorship care and expressed a desire for additional research. CONCLUSION: Our exploratory study suggests an awareness of cancer survivorship care in integrated health care delivery systems, although approaches to providing such care vary across systems. These settings may offer a unique opportunity to develop, test, and implement innovative models of care, which can be systematically evaluated to inform and enhance cancer survivorship care in diverse health care settings.